1974
DOI: 10.1029/ja079i013p01942
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational temperature and molecular density of thermospheric nitrogen measured by rocket-borne electron beam induced luminescence

Abstract: The vibrational temperature and molecular density of thermospheric nitrogen were probed in situ above Fort Churchill, Manitoba, Canada, on March 13, 1970. The rocket‐borne system utilized electron beam induced luminescence of the atmosphere as a diagnostic technique in effecting the measurements. The vibrational populations of N2+ ions in the B²Σu+ state were inferred from the intensities of selected transitions of the N2+ first negative (1N) band system (B²Σu+−X²Σg+) induced by a 2.5‐keV electron impact. Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 42 publications
(6 reference statements)
2
5
0
Order By: Relevance
“…deLeeuw andDavis (1972) applied the EBF technique for in situ measurement of N 2 T r in the lower thermosphere for the first time and built an instrument onboard a sounding rocket using an electron gun to excite and ionize ambient N 2 and two channel photomultipliers to detect the fluorescence from N + 2 . Around the same time, the first in situ measurement of N 2 T v has been done in aurora by O'Neil et al (1974) using a rocket-borne instrument that had an electron gun and four photometers. More than 20 years later, Kawashima et al, (1997Kawashima et al, ( , 1999 improved the instrument of O'Neil et al (1974) and obtained a continuous spectrum using a grating spectrometer with a linear image sensor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…deLeeuw andDavis (1972) applied the EBF technique for in situ measurement of N 2 T r in the lower thermosphere for the first time and built an instrument onboard a sounding rocket using an electron gun to excite and ionize ambient N 2 and two channel photomultipliers to detect the fluorescence from N + 2 . Around the same time, the first in situ measurement of N 2 T v has been done in aurora by O'Neil et al (1974) using a rocket-borne instrument that had an electron gun and four photometers. More than 20 years later, Kawashima et al, (1997Kawashima et al, ( , 1999 improved the instrument of O'Neil et al (1974) and obtained a continuous spectrum using a grating spectrometer with a linear image sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Around the same time, the first in situ measurement of N 2 T v has been done in aurora by O'Neil et al (1974) using a rocket-borne instrument that had an electron gun and four photometers. More than 20 years later, Kawashima et al, (1997Kawashima et al, ( , 1999 improved the instrument of O'Neil et al (1974) and obtained a continuous spectrum using a grating spectrometer with a linear image sensor. They measured T v and T r simultaneously using this instrument named "N 2 Temperature of Vibration" (NTV) onboard a sounding rocket S-310-24 over 100-160 km altitude range from Kagoshima, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…In the final N2(v = 1) state, however, approximately 1010 collisions are required to transfer one quantum of vibrational energy to kinetic energy [O'Neil et al, 1974]. In the final N2(v = 1) state, however, approximately 1010 collisions are required to transfer one quantum of vibrational energy to kinetic energy [O'Neil et al, 1974].…”
Section: N2(v = 0) + Nil(v = V')-"n2(v = 1) + N2(v = V'-1)mentioning
confidence: 99%
“…Although they did not include electron impact excitation of N 2 , Kummler and Bortner summarized the major mechanisms for producing vibrational excitation in N 2 . In a well conceived experiment, O'Neil et al [1974] launched a rocket into an IBC Class II aurora for the purpose of measuring the vibrational population distribution of the N 2 [X 1 Σ g + ] state in the altitude range 100–200 km (see Vallance Jones [1974] for a definition of the IBC auroral index and its relationship to other magnetic disturbance indices). Relative intensities of selected First Negative bands originating from vibrational levels 0, 1, and 2 of the upper electronic state of N 2 + were combined with a model for the direct electron impact excitation process from ground state N 2 to infer the initial vibrational population of the N 2 ground electronic state.…”
Section: Introductionmentioning
confidence: 99%
“…O'Neil et al concluded that the relative population of N 2 [X( ν ″ = 1)] “was not recognizably greater than that based on model atmospheric temperatures” but that the relative population of N 2 [X( ν ″ = 2)] was anomalously large. Eleven years later, Vlaskov and Henriksen [1985] reported results (from an analysis of ground based emission data from day and night side aurora) based on the same excitation model for N 2 + as used by O'Neil et al [1974] and relative intensities of the N 2 + 1st negative band system. The height of the dayside aurora was assumed to be 150 km and that for the night side aurora 350 km.…”
Section: Introductionmentioning
confidence: 99%